Stimulation of the Salt Receptor of the Blowfly : III. The alkali halides - Gillary, Howard L. (The Rockefeller University Press, 1966)
Application of solutions of each of the alkali halides to the tip of a labellar sensillum of the blowfly elicited a repetitive neural discharge from the salt receptor. The records were qualitatively similar to those for NaCl. For each of the alkali chlorides and sodium halides, the shapes of the curves of the response of the salt receptor as a function of concentration were similar to that for NaCl. The alkali halides exhibited a regular pattern of relative stimulating effectiveness for the salt receptor. The effectiveness of the anions increased monotonically with atomic number. The effectiveness of the cations was greatest for potassium and declined as the atomic number was increased or decreased. This hierarchy for stimulating effectiveness was maintained at all tested molarities. The response to a mixture of two salts appeared to be an average of those to the single salts at concentrations equal to the total concentration of the mixture. Cross-adaptation was observed between the alkali halides. The results indicate that an explanation of stimulation of the salt receptor must apply to all the salts tested and that both the anion and the cation affect a salt's stimulating effectiveness.